Phase Analysis of the Cellulose Triacetate-Nitromethane System - Anna B. Shipovskaya; Natalia O. Gegel; Sergei L. Shmakov; Sergei Yu. Shchyogolev (International Journal of Polymer Science)
A comprehensive study was made on the cellulose triacetate-nitromethane system to explore its phase separation within ranges 2–25 wt.% and −5÷+80°C by means of polarization light and electron microscopy, the turbidity spectrum method, differential thermal and X-ray analyses, and rheological techniques. The physical state of the polymer was identified within the phase coexistence boundaries on the phase diagram which included three types of phase separation (amorphous (with a UCST at Tcr=57∘C and ccr=7.3 wt.%), crystal, and liquid crystal). The boundaries of the regions determining the coexistence of the liquid crystal (LC) and the partly crystal phase were found to be inside the region of amorphous liquid-liquid phase separation. For cellulose ester-solvent systems, this state diagram is the first experimental evidence for the possibility of coexistence of several phases with amorphous, LC, and crystal polymer ordering.